Answer:
cosine
Step-by-step explanation:
Help u with what I need to know what u need help on
Answer:
Step-by-step explanation: 10 but thanks green guy
The first two negatives cancel out and you're left with positive 4. Now go inside the square root and do the exponent. -4*-4 = 16. Then do the -4*3*1 = -12. Do 16-12 = 4. now the square root of 4 = 2. at the dominator is 2*3 = 6. right now they problem should look like 4+- 2/ 6. from there you split the problem in two. so you have 4+2/6 & 4-2/6 then you solve both problems.
6/6 2/6
1 1/3
1 & 1/3 are your answers. I hope this helped!
(f*g)(x)=(x³-4x+2)(x²+2) = x⁵+2x³-4x³-8x+2x²+4=x⁵-2x³+2x²-8x+4